Using Game Theory to Understand Screening for Domestic Violence Under the TANF Family Violence Option - Soonok An; Jisung Yoo; Larry G. Nackerud (Advances in Social Work, 2016)
Universal screening for domestic violence in the Temporary Assistance for Needy Families (TANF) program is required by most states, but its implementation is questionable. This paper employs game theory to conceptualize interactions between TANF applicants and frontline eligibility caseworkers. The intended outcomes of universal screening for intimate partner violence (IPV) – granting of a good cause waiver to IPV victims – are valid only by the assumption that caseworkers perform their roles. To grant a good cause waiver, TANF applicants and caseworkers should exchange two types of information: 1) disclosure of abuse by IPV victims and 2) notification of the availability of good cause waivers by caseworkers. This paper illuminates that intended outcomes of universal screening for IPV are difficult to achieve and discusses the applicability and limitations of game theory for policy evaluation.